Moving Career Development Upstream: Evaluation of a Course for Internal Medicine Trainees Contemplating Career Pathways in Academic Medicine. Issue 8 (August 2018) - Kraemer, Ryan R.; Wakelee, Jessica F.; Hites, Lisle; Frank, Stuart J.; Saag, Kenneth; Rogers, David A.; Nellore, Anoma; Erdmann, Nathan; Nichols, Ashley C.; Merlin, Jessica S.
Abstract : Objectives: Despite training in academic medical centers, many residents and fellows lack an understanding of the different career paths in academic medicine. Without this fundamental knowledge, choosing an academic career pathway and transitioning to junior faculty is challenging. We started the Pathways in Academic Medicine course ("Pathways") to introduce residents and fellows to the wide array of academic career pathways and to expose them to the concepts and resources needed to transition successfully from trainee to junior faculty. Results: Sixty-nine medicine residents and fellows participated in Pathways programming. Surveys and focus groups revealed high satisfaction with the course sessions. Trainees indicated that Pathways helped them to envision an academic career, clarified the steps needed to pursue an academic career, and normalized common challenges. Conclusions: Pathways is an important educational innovation that gives participants experiences to jumpstart successful careers in academic medicine. We hope that our program will serve as an example for other institutions interested in improving the trainee-to-faculty transition. Abstract : Despite training in academic medical centers, many residents and fellows lack an understanding of the different career options in academic medicine. The authors created the Pathways in Academic Medicine course to introduce residents and fellows to the wide array of academic career paths and to expose them to the concepts and resources needed to transition successfully from trainee to junior faculty. Trainees indicated that the program helped them to envision an academic career, clarified the steps needed to pursue an academic career, and normalized common challenges.